Vibration of orthotropic plates: Discussion on the completeness of the solutions used in direct methods - Rosales, Marta Beatriz (2003)
The importance of the completeness of a set of solutions used in a direct variational method is herein discussed regarding a plate vibration application. The property is relevant to two issues: the claim of an “exact” solution and the avoidance of the loss of eigenfrequencies.